The vascular armamentarium explored-the ultimate goal achieved - Ravichandran, Manoj Prabakar; Rathinavelpandian, Subrammaniyan; Gnanasekaran, Marunraj; Balachandran, Saravanan (International Surgery Journal, 2020)
Peripheral arterial disease is one of the commonest causes for a limb being amputated most often, we present this case of medium vessel vasculitis with chronic threatening limb ischemia to make a note of our attempt to save her limb by multiple modalities which included medical management with steroids, immunosuppressants, pulsed cyclophosphamide, interventional radiological procedure of catheter directed thrombolysis with urokinase, surgical procedures like bypass, split skin grafting and minor amputations, implemented novel modalities like hyperbaric oxygen therapy. By exploring the armamentarium available, involving a multidisciplinary team which included vascular surgeon, rheumatologist, intervention radiologist, plastic surgeon, physiotherapist and aptly using the right modality at the right time we were able to ultimately achieve our goal of limb salvage.